Body Count: The War on Terror and Civilian Deaths in Iraq, by Lily Hamourtziadou – Book Review - Alannah Travers (Journal of Global Faultlines)
Body Count: The War on Terror and Civilian Deaths in Iraq is essential reading for anyone interested in understanding the true impact of the Iraq War and its ongoing consequences for the people of Iraq. Lily Hamourtziadou has created a powerful account of the human cost of war, and her dedication to truth and justice is evident on every page. Body Count is both a work of immense scholarly value, and a tribute to the individuals who have suffered and continue to suffer as a result of the conflict. https://bristoluniversitypress.co.uk/body-count